2011
DOI: 10.1007/s10928-011-9219-z
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic–pharmacodynamic–disease progression model for effects of anakinra in Lewis rats with collagen-induced arthritis

Abstract: A population pharmacokinetic–pharmacodynamic–disease progression (PK/PD/DIS) model was developed to characterize the effects of anakinra in collagen-induced arthritic (CIA) rats and explore the role of interleukin-1β (IL-1β) in rheumatoid arthritis. The CIA rats received either vehicle, or anakinra at 100 mg/kg for about 33 h, 100 mg/kg for about 188 h, or 10 mg/kg for about 188 h by subcutaneous infusion. Plasma concentrations of anakinra were assayed by enzyme-linked immunosorbent assay. Swelling of rat hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
(68 reference statements)
2
18
1
Order By: Relevance
“…Estimates of most DIS-related parameters, such as t onset and k grow , were close to the previously reported values. However, the baseline rat paw volume ( Paw 0 ) in our current study (55.4 mm 2 ) was slightly lower than those in the etanercept (~62.6 mm 2 ) [13] and anakinra (57.1 mm 2 ) studies [14]. This reflects batch-to-batch differences in the rats and emphasized the importance of considering inter-individual variability in our modeling analysis.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Estimates of most DIS-related parameters, such as t onset and k grow , were close to the previously reported values. However, the baseline rat paw volume ( Paw 0 ) in our current study (55.4 mm 2 ) was slightly lower than those in the etanercept (~62.6 mm 2 ) [13] and anakinra (57.1 mm 2 ) studies [14]. This reflects batch-to-batch differences in the rats and emphasized the importance of considering inter-individual variability in our modeling analysis.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, such dosing groups were added to our subsequent studies with anakinra [14], methotrexate (MTX) [41], and abatacept. The doses selected in our studies were based on previous findings that showed successful use of the drug in similar animal models [39,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of model can be seen in Liu et al (25) who developed a combined PKPD and disease progression model to evaluate the effect of anakinra in collagen-induced arthritic rats and to explore the effect of interleukin-1β in rheumatoid arthritis. Having a combined PKPD and disease progression model in a validated AMD may be an ideal situation as it allows for an integrated understanding of exposure, response, and disease progression in a single system and reduces uncertainty and variability in the translation.…”
Section: Pkpd Relationship In the Animal Model Of Diseasementioning
confidence: 99%